2D Materials for Cardiac Tissue Repair and Regeneration - Cemile Gokce; Cansu Gurcan; Cansu Gurcan; Lucia Gemma Delogu; Acelya Yilmazer; Acelya Yilmazer (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases (CVDs) have a massive impact on human health. Due to the limited regeneration capacity of adult heart tissue, CVDs are the leading cause of death and disability worldwide. Even though there are surgical and pharmacological treatments for CVDs, regenerative strategies are the most promising approaches and have the potential to benefit millions of people. As in any other tissue engineering approach, the repair and regeneration of damaged cardiac tissues generally involve scaffolds made up of biodegradable and biocompatible materials, cellular components such as stem cells, and growth factors. This review provides an overview of biomaterial-based tissue engineering approaches for CVDs with a specific focus on the potential of 2D materials. It is essential to consider both physicochemical and immunomodulatory properties for evaluating the applicability of 2D materials in cardiac tissue repair and regeneration. As new members of the 2D materials will be explored, they will quickly become part of cardiac tissue engineering technologies.